Adipocytes Directly Affect Coronary Artery Disease Pathogenesis via Induction of Adipokine and Cytokine Imbalances - Gruzdeva, Olga; Uchasova, Evgenya; Dyleva, Yulia; Borodkina, Daria; Akbasheva, Olga; Antonova, Larisa; Matveeva, Vera; Belik, Ekaterina; Ivanov, Sergei; Sotnikov, Anton; Kozyrin, Kirill; Brel, Natalia; et al. (Frontiers in Immunology, 2019)
Abstract This study aimed to investigate the adipokine and cytokine profiles of adipocytes from epicardial and subcutaneous adipose tissues in interconnection with the visceral adipose tissue area and the biochemical and clinical characteristics of patients with coronary artery disease. We assessed 84 patients with coronary artery disease (65 men, 19 women) and divided them into two groups based on the presence of visceral obesity. We sampled epicardial and subcutaneous adipose tissues from the patients with visceral obesity. We then cultured the adipocytes and evaluated their adipokine profiles and pro-inflammatory activity. Results show that the mRNA expression of adiponectin in cultures of epicardial adipocytes from patients with and without visceral obesity was lower than that in subcutaneous adipocytes. Moreover, adiponectin mRNA expression in cultures of subcutaneous and epicardial adipocytes from patients with visceral obesity was lower than that in patients without obesity. For leptin, the reverse pattern was observed, with expression higher in cultures of epicardial adipocytes than in subcutaneous adipocytes and higher in epicardial adipocytes from patients with visceral obesity than in those from subjects without visceral obesity. In addition, in epicardial adipocytes, increased expression of proinflammatory cytokine genes (IL6, TNF) was observed compared with that in subcutaneous adipocytes. In contrast, expression of IL10 was higher in cultures of subcutaneous adipocytes than in epicardial adipocytes. The epicardial adipose tissue area was associated with the presence of higher levels of leptin and TNF-α within adipocytes and serum, increased lipid and carbohydrate metabolism. Coronary artery disease, in the context of the status of epicardial adipocytes, can be characterised as ‘metabolic inflammation’, suggesting the direct involvement of adipocytes in pathogenesis through the development of adipokine imbalances and activation of proinflammatory processes.